2004
DOI: 10.1172/jci200421109
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I is a selective target for myeloperoxidase-catalyzed oxidation and functional impairment in subjects with cardiovascular disease

Abstract: In recent studies we demonstrated that systemic levels of protein-bound nitrotyrosine (NO(2)Tyr) and myeloperoxidase (MPO), a protein that catalyzes generation of nitrating oxidants, serve as independent predictors of atherosclerotic risk, burden, and incident cardiac events. We now show both that apolipoprotein A-I (apoA-I), the primary protein constituent of HDL, is a selective target for MPO-catalyzed nitration and chlorination in vivo and that MPO-catalyzed oxidation of HDL and apoA-I results in selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
354
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(394 citation statements)
references
References 99 publications
21
354
0
5
Order By: Relevance
“…We and others have previously shown that HDL isolated from atherosclerotic lesions contains higher levels of oxidized amino acids than HDL isolated from plasma (10)(11)(12). This observation raises the possibility that proteins found in HDL from CAD patients might come in part from the artery wall.…”
Section: Figurementioning
confidence: 75%
See 1 more Smart Citation
“…We and others have previously shown that HDL isolated from atherosclerotic lesions contains higher levels of oxidized amino acids than HDL isolated from plasma (10)(11)(12). This observation raises the possibility that proteins found in HDL from CAD patients might come in part from the artery wall.…”
Section: Figurementioning
confidence: 75%
“…Moreover, both oxidative modifications and alterations in the protein cargo of HDL may alter its biological activity, creating potentially proatherogenic particles (8,9). We and others recently showed that HDL isolated from plasma of patients with known coronary artery disease (CAD) is oxidatively modified and that oxidation impairs reverse cholesterol transport mediated by HDL (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The strong cationic enzyme MPO interacts easily with acidic proteins such as albumin, a 1 -antiproteinase, fibronectin, apolipoprotein A-1 and ceruloplasmin [25,[29][30][31][32][33][34]. Attachment of MPO to negatively charged membrane sites have also been reported whereby a heparin-heparan-binding site was assumed [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) replaces apoA-I in HDL particles, generating lipid-free apoA-I, which is more rapidly cleared by the kidney [21•]. Leukocyte myeloperoxidase-induced oxidation also generates "dysfunctional" HDL-C with pro-inflammatory properties and with a reduced ability of apoA-I to promote cholesterol efflux via ABCA1 [22]. Finally, non-enzymatic glycation of apoA-I has been shown to impair its ability to promote ABCA1 stabilization and ABCA1-dependent cholesterol efflux, and activation of LCAT and its anti-inflammatory properties [23].…”
Section: Hdl Function Is Affected In Certain Pathophysiologic Statesmentioning
confidence: 99%